An Analysis of Conceptual Metaphor in “Dear Evan Hansen: The Novel” - Anone, Nanda Jesica Natalia Yuliani; I Gusti Ayu Vina Widiadnya Putri; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Metaphor is one of figurative language which compares one different thing to another. This study is focused on the types of conceptual metaphor used in “Dear Evan Hansen: The Novel” by Val Emmich, Steven Levenson, Benj Pasek, and Justin Paul. The purpose of this research is to identify the types of conceptual metaphor used by the author in both the dialogue and the narrative text in the book. This research used descriptive qualitative method to manage a clear and systematic description about the metaphor found in the book “Dear Evan Hansen: The Novel”. The data were collected from the digital book and were elaborated based on the theory proposed by Lakoff and Johnson (1980) about conceptual metaphor. Based on the acquired data, there are 155 conceptual metaphors were identified in the book “Dear Evan Hansen: The Novel”, including structural metaphor, orientational metaphor, and ontological metaphor.